Laboratory genetic-based reference values for cholinesterase activity in a Colombian population: A step forward in personalized diagnostics. - Sánchez, Luz Helena; Medina, Olga Marcela; Gómez, Guillermo; González, Clara Isabel; Flórez-Vargas, Óscar (Biomédica: Revista del Instituto Nacional de Salud)
Introduction: The determination of cholinesterase (ChE) activity has been commonly applied in the biomonitoring of exposure to organophosphate and carbamate pesticides. However, ChE activity is influenced by genetic factors. Integrating genotype and phenotype information in clinical laboratory tests would increase the accuracy of the reference values in well-defined populations. Objective: To establish genetic-based reference values for acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activity in a Colombian population. Materials and methods: A total of 397 healthy adults from Bucaramanga were included in the study. AChE and BChE activities were measured in blood samples by potentiometry and spectrophotometry, respectively. Genotyping for ACHE rs17880573 and BCHE rs1803274 was performed using the TaqMan allelic discrimination assay. The statistical analyses to obtain the reference values were performed with the MedCalc® software. Results: Allele frequencies were 10.58% for rs17880573 A and 8.82% for rs1803274 A. People with genotypes rs1803274 AA and AG showed a reduction of 20.69% and 10.92% respectively in mean BChE activity compared to people with genotype GG. No significant differences were identified in AChE activity between rs17880573 alleles or genotypes. In the overall sample, the corresponding reference values were as follows: for AChE activity, 0.62-0.98 pH/h and for BChE activity, 4796.3-10321.1 U/L for people carrying the allele rs1803274A and 5768.2-11180.4 U/L for people carrying the genotype rs1803274 GG. Conclusion: We strongly recommend using these genetic-based reference values for ChE enzymes in our well-defined population in daily clinical practice.